2006
DOI: 10.1016/j.rmedu.2006.01.019
|View full text |Cite
|
Sign up to set email alerts
|

A functional mutation in the terminal exon of elastin in severe, early onset chronic obstructive pulmonary disease

Abstract: We describe a novel variant in the terminal exon of human elastin, c.2318 GϾA, resulting in an amino acid substitution of glycine 773 to aspartate (G773D) in a pedigree with severe early-onset chronic obstructive pulmonary disease (COPD). Transfection studies with elastin cDNAs demonstrate that the glycine to aspartate change compromises the ability of the mutant protein to undergo normal elastin assembly. Other functional consequences of this amino acid substitution include altered proteolytic susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 31 publications
0
27
0
3
Order By: Relevance
“…In a previous study, we described a rare, missense variant of elastin (G773D) in a pedigree with severe early onset emphysema (25). This single amino acid change compromises the ability of the mutant protein to undergo normal elastin assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we described a rare, missense variant of elastin (G773D) in a pedigree with severe early onset emphysema (25). This single amino acid change compromises the ability of the mutant protein to undergo normal elastin assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Intrapulmonary instillation of elastolytic enzymes, for example, confirmed that destruction of existing elastic fibers leads to emphysema-like lesions (24,27,46). There is also evidence that functional variants of elastin may increase lung susceptibility to cigarette smoke-induced damage by altering elastic fiber assembly and integrity (25). More recently, experiments in mice have shown that deficiency in elastin or in the elastic fiber proteins fibrillin-1, LTBP-3 and -4, fibulin-4 and -5, and EMILIN (elastin microfibril interface located protein) all result in emphysema-like lung morphology at birth (6,35,36,49,51,56,58).…”
mentioning
confidence: 95%
“…It has been shown that a polymorphism of MMP-9 (C-1562T) is associated with upper lung dominant emphysema [50,51]. In addition, a genetic predisposition for proteolysis of elastin in connection with the expression of a variant of the terminal exon in human elastin has been described for patients with severe COPD [52]. The interest shown in the gene coding for phospholipase A 2 , a protein involved in the metabolism of fatty acids, is related to the fact that the plasma concentration of this enzyme is high in a certain number of inflammatory diseases [53].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Most elastin mutations associated with this disease are single nucleotide deletions near the 3Ј end of the gene 9 -11 resulting in missense sequence that alters the character of a biologically important domain at the end of the tropoelastin molecule. 12 ELN has also been suggested to be a susceptibility gene for hypertension, 13 emphysema, 14 and intracranial aneurysms. 15 ELN encodes a protein made up of alternating hydrophobic and crosslinking domains.…”
mentioning
confidence: 99%